Prognostic value of platelet to lymphocyte ratio (PLR) in breast cancer patients receiving neoadjuvant therapy: a systematic review and meta-analysis - Zhao, Ziqian; Xu, Haoyi; Ma, Binlin; Dong, Chao (Frontiers in Immunology, 2025)
BackgroundThe platelet to lymphocyte ratio(PLR) is widely recognized as an important biomarker of systemic inflammation and has been associated with treatment responses in breast cancer (BC) patients undergoing neoadjuvant therapy. However, existing evidence remains inconsistent. This meta-analysis aims to systematically investigate the prognostic value of PLR in BC patients receiving neoadjuvant chemotherapy (NACT).MethodsA broad and systematic search of the literature was carried out using PubMed, Embase, Web of Science, and the Cochrane Library, covering all available records from the inception of each database through April 7, 2025. Study selection was guided by a set of predetermined inclusion and exclusion parameters. Primary outcomes included overall survival (OS), disease-free survival (DFS), and pathological complete response (pCR), assessed through hazard ratios (HRs) or odds ratios (ORs) with corresponding 95% confidence intervals (CIs).ResultsTwenty-four studies involving 7,557 BC patients receiving NACT were included. Elevated PLR was significantly associated with reduced pCR rates (HR = 1.51; 95% CI: 1.24–1.84; p < 0.0001; I² = 70%), shorter OS (HR = 1.64; 95% CI: 1.27–2.11; p = 0.0002; I² = 0%), and decreased DFS (HR = 2.29; 95% CI: 1.54–3.39; p < 0.0001; I² = 44%). Subgroup analyses indicated that PLR’s prognostic value varied by timing of PLR measurement, geographic location, and PLR cutoff values.ConclusionsElevated PLR is significantly correlated with poorer clinical outcomes in BC patients undergoing NACT, suggesting its potential as a predictive biomarker for treatment efficacy. However, due to methodological limitations of the included studies, further prospective investigations are required to confirm these findings across diverse populations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251064051.